PENGARUH LIKUIDITAS, PROFITABILITAS, RISIKO BISNIS DAN INVESTMENT OPPORTUNITY SET (IOS) TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN IDX 80 PERIODE 2019 - 2023) - Larozsa, Nadina; Kamaliah, Kamaliah; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
The purpose of this study is to determine the effect of liquidity, profitability,business risk and investment opportunity set (IOS) on company value in IDX 80companies 2019 - 2023. This study was conducted on companies included in IDX80. The population in this study were IDX 80 companies 2019 - 2023, while thesample in this study amounted to 37 companies with purposive samplingtechnique. Data analysis using multiple linear regression. The results of the studyexplain that liquidity, profitability and business risk have a significant influence,while investment opportunity set (IOS) has no significant effect on company value.The results of the determination coefficient explain that liquidity, profitability,business risk and investment opportunity set (IOS) can affect company value inIDX 80 companies for the 2019-2023 period by 10.6% while the remaining 89.4%is influenced by other variables not examined in this study.Keywords: Liquidity, Profitability, Business Risk, Investment Opportunity Set(IOS) and Company Value.